1997
DOI: 10.1002/srin.199701773
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermomechanical treatment on medium‐carbon microalloyed steels continuously cooled from forging temperature

Abstract: In the high‐production‐drop‐forging of parts for automobile and truck engines the classical quench and tempering (QT) of low‐alloyed steels is nowadays ‐ in a lot of plants in Europe ‐ substituted by direct continuous cooling (CC) of microalloyed steels without the necessity of additional heat treatment and expensive straightening as well as stress relieving cycles. Nevertheless, there are some limitations on strength and toughness achievable by this technique. On two commercial medium‐carbon (0.3%C) steels mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Of the three aforementioned factors, the variation of post-forging cooling conditions could obtain different microstructural characteristics and thus has an extraordinary influence on the final mechanical properties of MA steels [2][3][4][5][8][9][10]. Increasing cooling rate enhances grain refinement and increases the proportion of hard phase of pearlite or the formation of high hardness phases such as bainite and martensite.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Of the three aforementioned factors, the variation of post-forging cooling conditions could obtain different microstructural characteristics and thus has an extraordinary influence on the final mechanical properties of MA steels [2][3][4][5][8][9][10]. Increasing cooling rate enhances grain refinement and increases the proportion of hard phase of pearlite or the formation of high hardness phases such as bainite and martensite.…”
Section: Introductionmentioning
confidence: 98%
“…For MA steels, it also significantly influences the precipitation hardening effect of microalloying elements [4]. Therefore, different post-forging cooling methods have been used to optimize the mechanical properties of MA steels [1,2,[11][12][13]. Initially, direct continuous cooling after finish forging was utilized to improve mechanical properties [1,2,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a two-step cooling and annealing (TSCA) treatment following controlled forging was developed to produce multiphase (ferrite-bainite-martensite, F-B-M) microstructures that displayed tensile properties similar to those of Q&T steels. It was reported that a decrease in the final deformation temperature led to a finer grain size (beneficial for toughness) and also promoted the formation of ferrite , 1998Kaspar et al, 1997). As part of a detailed investigation to develop better fatigue resistant and cost effective MA steels through process control, the processing parameters of the TSCA treatment (finish forging temperature, quenching temperature, annealing temperature and time) were optimized to get the desired microstructure and tensile properties in the medium carbon microalloyed steel 38MnSiVS5 (Sankaran et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a decrease in the final deformation temperature led to a finer grain size (beneficial for toughness) and also promoted the formation of ferrite. [3,4,5] The present investigation forms a part of an attempt to improve the tensile properties and the fatigue resistance of the automotive grade microalloyed steel 38MnSiVS5 through thermomechanical processing to produce a F-B-M microstructure. [6][7][8][9] Here an attempt was made to optimize the parameters (finish forging temperature, quenching temperature, annealing temperature and time) of the TSCA treatment.…”
Section: Introductionmentioning
confidence: 99%